Adsorption and Detection of Hazardous Trace Gases by Metal–Organic Frameworks. Issue 37 (19th June 2018) - Woellner, Michelle; Hausdorf, Steffen; Klein, Nicole; Mueller, Philipp; Smith, Martin W.; Kaskel, Stefan
Abstract: The quest for advanced designer adsorbents for air filtration and monitoring hazardous trace gases has recently been more and more driven by the need to ensure clean air in indoor, outdoor, and industrial environments. How to increase safety with regard to personal protection in the event of hazardous gas exposure is a critical question for an ever‐growing population spending most of their lifetime indoors, but is also crucial for the chemical industry in order to protect future generations of employees from potential hazards. Metal–organic frameworks (MOFs) are already quite advanced and promising in terms of capacity and specific affinity to overcome limitations of current adsorbent materials for trace and toxic gas adsorption. Due to their advantageous features (e.g., high specific surface area, catalytic activity, tailorable pore sizes, structural diversity, and range of chemical and physical properties), MOFs offer a high potential as adsorbents for air filtration and monitoring of hazardous trace gases. Three advanced topics are considered here, in applying MOFs for selective adsorption: (i) toxic gas adsorption toward filtration for respiratory protection as well as indoor and cabin air, (ii) enrichment of hazardous gases using MOFs, and (iii) MOFs as sensors for toxic trace gases and explosives. Abstract : Filtration, enrichment, and sensing of toxic gases and vapors using metal–organic frameworks (MOFs) are currently studied by many researchers. To meet increasing demands regarding air quality and safety issues, new functional materials are required. MOFs show great potential to overcome the drawbacks of state‐of‐the‐art materials in regard to air filtration and monitoring of hazardous trace gases.